mortgage and MBS--the case of Shanghai - LI, YIJIA (2007)
The paper divided to 6 parts. The first one introduces the history and current status of commodity housing. Shanghai has a fast growing and bright forecasting. It follows with a discussion on Shanghai housing bubble, which involve the reason, implications and reactions of government, normal purchaser and speculators.